Ngugi's Critical Consciousness Turn in Devil on the Cross - Wang, Xuan (International Journal of Global Economics and Management, 2024)
Ngugi wa Tiango's novel Devil on the Cross employs a variety of oral elements of Kikuyu tradition as anti-colonising linguistic strategies. This paper intends to explain Ngugi's subversion of the traditional Western narrative discourse by the narrative mode constructed in national discourse from the anti-colonising linguistic strategy that the novel has. It examines the critical consciousness behind Ngugi's anti-colonial linguistic strategy, explores the realistic concern in the novel's historical context, and reveals the anti-colonial consciousness and critical consciousness turn in the novel's linguistic strategy.